2012
DOI: 10.1002/uog.10058
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound imaging and measurement of nasal bone length, prenasal thickness and frontomaxillary facial angle in normal second‐ and third‐trimester fetuses

Abstract: Objectives To assess the feasibility of nasal bone length (NBL), prenasal thickness (PT) and frontomaxillary facial (FMF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 13 publications
(30 reference statements)
4
42
2
6
Order By: Relevance
“…This finding may be due to the relatively small sample size however it is consistent with the findings of a number of studies, three between 11 and 14 weeks [10,16,17] and another in the second and third trimester [18] all of which have cohorts of over 200 patients. This differs from the conclusions of several earlier studies [15,17,19,20] possibly due to inclusion of the frontal process of the maxillary bone for optimal caliper placement in more recent studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding may be due to the relatively small sample size however it is consistent with the findings of a number of studies, three between 11 and 14 weeks [10,16,17] and another in the second and third trimester [18] all of which have cohorts of over 200 patients. This differs from the conclusions of several earlier studies [15,17,19,20] possibly due to inclusion of the frontal process of the maxillary bone for optimal caliper placement in more recent studies.…”
Section: Discussionsupporting
confidence: 75%
“…Accurate and reliable FMFA measurement in both 2D and 3D imaging modes is possible by concentrating on appropriate training and strict adherence to rigorous imaging criteria [14,18]. A successful 2D and 3D FMFA measurement training program would require the development of appropriate auditable standards, possibly including statistical analysis of the 95% limits of agreement between trainees and experienced operators as well as assessing the distribution and spread of an individual's FMFA measurements, before competency could be established [14].…”
Section: Discussionmentioning
confidence: 99%
“…16 Many researchers have reported in the literature that nasal bone length increased in parallel with the gestational age. [15][16][17] In present study, nasal bone length was detected as 8.30±2.20mm in male fetuses and as 7.97±1.53mm in female fetuses. The difference between the literature and our study was originated from gestational age difference.…”
Section: Discussionsupporting
confidence: 53%
“…Data were compared with the reference values derived from our previous reports on euploid fetuses [14,19] or compared with reference values derived from the literature [8,9,22,23]; the NBL and PT increased with gestation from 3.3 mm at 15 weeks' gestation to 9.6 mm at 33 weeks (NBL = -6.927+(0.83*GA)-(0.01*GA 2 )) and from 2.3 mm at 15 weeks to 6.1 mm at 33 weeks (PT = 0.212 × GA − 0.873), respectively. The PT-NBL ratio and PFSR were stable throughout gestation, with a mean of 0.61 (95th centile = 0.80) and 0.97 (5th centile = 0.55), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we have demonstrated that the NBL, PT, PT-NBL ratio, and PFSR are valuable and reproducible DS markers [13,14,19] and assessed the detection rates, which appear to be evenly distributed throughout the second and third trimester. However, these studies were based on cross-sectional measurements in both normal and DS fetuses.…”
Section: Introductionmentioning
confidence: 99%